Chronic Pulmonary Aspergillosis: Clinical Presentation and Management - Evans, Terry J.; Lawal, AbdulAzeez; Kosmidis, Chris; Denning, David W. (Seminars in Respiratory and Critical Care Medicine, 2023)
Chronic pulmonary aspergillosis (CPA) refers to a number of clinical syndromes resulting from the presence and local proliferation of Aspergillus organisms in the lungs of patients with chronic lung disease. CPA is more common than was realized two decades ago. Recognition remains poor, despite recent studies from many countries highlighting the high prevalence in at-risk populations. In low- and middle-income countries, CPA may be misdiagnosed and treated as tuberculosis (TB). In addition, CPA may develop following successful TB treatment. The coronavirus disease pandemic has resulted in significant disruption to provision of TB care, likely leading to more extensive lung damage, which could increase the risk for CPA.Although CPA refers to various syndromes, the classic presentation is that of chronic cavitary pulmonary aspergillosis, which manifests as one or more progressive cavities with or without a fungal ball, accompanied by systemic and respiratory symptoms for at least 3 months. Diagnosis relies on Aspergillus immunoglobulin G in serum, as sputum culture lacks sensitivity. Differential diagnosis includes mycobacterial infection, bacterial lung abscess or necrotizing pneumonia, lung cancer, and endemic fungi.The aim of antifungal treatment in CPA is to improve symptoms and quality of life, and to halt progression, and possibly reverse radiological changes. Current recommendations suggest treatment for 6 months, although in practice many patients remain on long-term treatment. Improvement may manifest as weight gain and improvement of symptoms such as productive cough, hemoptysis, and fatigue. Surgical management should be considered in cases of diagnostic uncertainty, in significant hemoptysis, and when there is concern for lack of response to therapy. Itraconazole and voriconazole are the first-line azoles, with more experience now accumulating with posaconazole and isavuconazole. Side effects are frequent and careful monitoring including therapeutic drug monitoring is essential. Intravenous antifungals such as echinocandins and amphotericin B are used in cases of azole intolerance or resistance, which often develop on treatment. Relapse is seen after completion of antifungal therapy in around 20% of cases, mostly in bilateral, high-burden disease.Several research priorities have been identified, including characterization of immune defects and genetic variants linked to CPA, pathogenetic mechanisms of Aspergillus adaptation in the lung environment, the contribution of non-fumigatusAspergillus species, and the role of new antifungal agents, immunotherapy, and combination therapy.
Keywords: Aspergillus fumigatus; azole resistance; hemoptysis; lobectomy; micafungin